Strategic thinking : What, why and how - Hashim, Mohd Khairuddin; Zakaria, Mustafa; Hamdan, Oemar (Jurusan Akuntansi Fakultas Ekonomi Universitas Lampung, 2005)
Strategic thinking is increasingly being recognized as an important requirement for effective strategic management in business organizations. More and more scholars, consultants and practitioners are conceding that strategies. Despite being considered as an integral part of the strategic management process, the literature indicates strategic thinking has not received much research attention. This paper strives to address this gap. Specifically, the paper attempts to provide some useful insight into the development of strategic thinking as an important strategic management concept and good business practice.